The predictors of student performance in a blended learning environment at Higher Education Institutions (HEIs) in Tanzania: a case study conducted at the University of Dar-es-Salaam - Kabudi, Tumaini John (Rhodes University, Faculty of Commerce, Department of Information Systems, 2019)
Blended Learning is an important technological platform which has the potential to enhance the efficiency and efficacy of educational provision, especially in Tanzania universities. Despite a high level of investment into Blended learning, students face various challenges that have impeded them performing well in Blended learning courses. The purpose of this research is to examine and explore how student's performance in a Blended learning environment is influenced by motivation and learning strategies; using the University of Dar es Salaam as a case study. This is a pragmatic research that utilises a mixed research design. The research design includes both qualitative design (in-depth single case study) and quantitative design (survey). The target population for this study is students participating in Blended learning modules. Primary data will be collected by means of Motivational Strategies for Learning Questionnaire and observation. It was found that motivation and learning strategies are significant predictors of student performance in a Blended learning environment. In terms of the motivation categories, Intrinsic Goal Orientation and Self-efficacy have statistically significant effect on student performance. With learning strategies sub factors, it was found out that Rehearsal, Effort Regulation and Peer Learning have significance effect on student performance. Moreover, age and gender significantly influence performance. The findings obtained are significant in building a better understanding of the influence that the mentioned predictors have on predicting the performance of students in Blended learning courses in Tanzania.
Keywords: Prediction of scholastic success -- Tanzania -- Case studies; Motivation in education -- Tanzania -- Case studies; Academic achievement -- Tanzania -- Case studies; Blended learning -- Tanzania -- Case studies; Chuo Kikuu cha Dar es Salaam -- Students